Morphological evidence for a neurotensinergic periaqueductal gray-rostral ventromedial medulla-spinal dorsal horn descending pathway in rat - Wang, Jian; Zhang, Hua; Feng, Yu-Peng; Meng, Hua; Wu, Li-Ping; Wang, Wen; Li, Hui; Zhang, Ting; Zhang, Jin-Shan; Li, Yun-Qing (Frontiers in Neuroanatomy, 2014)
Neurotensin (NT) is an endogenous neuropeptide that exerts potent opioid-independent analgesic effects, most likely via the type 2 NT receptor (NTR2). Previous morphological and electrophysiological studies suggested that the NT-NTR2 system is primarily localized in structures that constitute the descending pain control pathway, such as the periaqueductal gray (PAG), the rostral ventromedial medulla (RVM), and the spinal dorsal horn (SDH). However, relevant morphological evidence for this neurotensinergic (NTergic) circuit is lacking. Thus, the aim of the present study was to morphologically elucidate the potential sites and connections in the NT-NTR2 system that are involved in the descending pain control pathway. Based on light and electron microscopy combined with anterograde and retrograde tracing, we found evidence that NTR2-immunoreactive (IR) neurons in the RVM receive NT-IR projections originating from the PAG; express NT, serotonin (5-HT), or both; and send projections that terminate in laminae I and II of the SDH. These results suggest that NTR2 may contribute to pain control by binding to NT in the PAG-RVM-SDH pathway. In conclusion, our data provide morphological evidence for an NTergic PAG-RVM-SDH pathway, implicating novel mechanisms of NT-induced analgesia.